'Like a Dance': Working creatively with healthcare practitioners to explore mobility and osteoporosis. (1st December 2019) - Smith, Margaret A. Coulter; Schrag, Anthony; Kelly, Fiona; Pearson, Claire
AbstractCollaborations between health sciences and creative arts can generate insights into complex health phenomena. This article describes a creative workshop derived from an action research project that aimed to raise awareness of fracture risk in health practitioners supporting people with osteoporosis. The creative workshop aimed to provide opportunities for practitioners within the action research community to create new knowledge and share their practice insights. The article considers the notion of creative arts as a physical, embodied process that can facilitate learning by enabling tacit knowledge to be made explicit. Rather than applying an instrumental approach to arts within healthcare, the workshop became a mechanism for the convergence of ideas, disciplines and support structures and provided a learning environment where old beliefs could be challenged, practice insights shared and new knowledge constructed. We discuss the workshop development and outputs and suggest the utility of this approach for collaborative learning.